TNF inhibitor treatment is associated with a lower risk of hand osteoarthritis progression in rheumatoid arthritis patients after 10 years. (19th February 2018) - Loef, Marieke; Kroon, Féline P B; Bergstra, Sytske Anne; van der Pol, Joy A; Lems, Willem F; Kerstens, Pit J S M; Allaart, Cornelia F; Kloppenburg, Margreet
Abstract: Objective: To investigate the effect of TNF inhibitors (TNFis) on incidental and progressive hand OA in recent-onset RA patients after a 10 year follow-up. Methods: Radiographs of 262 RA patients (mean age 52 years, 66% women) from the BeSt study were scored for osteophytes in DIP/PIP joints using the Osteoarthritis Research Society International atlas (0–3; summed score 0–54) and according to the Kellgren–Lawrence (KL) score (0–4; summed score 0–72) at baseline and 10 year follow-up. TNFi treatment was assessed on visits every 3 months. Associations between TNFi treatment and hand OA were analysed on the patient and joint level using generalized linear models and generalized estimating equations, respectively. Results: Fifty-eight percent of the patients were treated with TNFi, with a median duration of 42 months. A total of 143 patients (55%) had hand OA in any IP joint at baseline based on the Osteoarthritis Research Society International osteophyte score. On the patient level, TNFi treatment duration did not affect incidental hand OA. However, every month of TNFi treatment resulted in a reduced relative risk (RR) of hand OA progression in DIP joints [relative risk (RR) 0.987 (95% CI 0.978, 0.996)] but not in PIP joints. On the joint level, the effect on hand OA progression was observed in DIP joints [RR 0.996 (95% CI 0.991, 1.000)] but not in PIP joints. The results from the KL score analyses were comparable to the osteophyte score. Conclusion: TNFi treatment was associated with a reduced risk on radiographic hand OA progression in DIP joints but not in PIP joints after 10 years. Although the effect sizes are small, these results provide evidence for influence of TNF-α in hand OA pathogenesis.